Mid-infrared optical coherence tomography and machine learning for inspection of 3D-printed ceramics at the micron scale - Heise, Bettina; Zorin, Ivan; Duswald, Kristina; Karl, Verena; Brouczek, Dominik; Eichelseder, Julia; Schwentenwein, Martin (Frontiers in Materials, 2024)
Here, information is provided for the inspection of 3D printed ceramics in a non-destructive way and for monitoring additive manufacturing (AM) of ceramics. Especially, a design and use of an inline Mid-infrared (MIR) Optical Coherence Tomography (OCT) system is presented, focused on printed and micro-structured specimens in lithography-based ceramic manufacturing (LCM). The detection of micro-defects (e.g., voids, inclusions, deformations) already in green ceramics parts saves energy and costs. The challenges of integration are discussed and perspectives for MIR-OCT imaging combined with machine learning (ML) are illustrated for inline inspection in LCM process of printed ceramics.